ANALISIS DISIPLIN KINERJA KARYAWAN PADA CV. BABY MINISTRY INDONESIA DI KOTA TANGERANG SELATAN - Dina Lafenia Elissia; Jazuli Mukhtar; Mukhamad Khotib Arifai (Journal of Research and Publication Innovation, 2024)
This research aims to determine the implementation of employee performance discipline at Cv. Baby Ministry Indonesia in South Tangerang City and know the SWOT form in disciplining employee performance at CV. Indonesian Baby Ministry in South Tangerang City. This research uses a descriptive qualitative approach. The data collection techniques used in this research are observation, interviews and documentation. Apart from that, this research uses SWOT data analysis to analyze the company's strengths, weaknesses, opportunities and threats. The results of the research are: there are strict sanctions and punishments, when employees arrive late or leave earlier than their usual leaving time and there are differences in performance hours between employees.